Modeling of the pattern of hydrological phenomena in climate conditions using fractal theory and entropy criterion - Mehdi Komasi; Bahareh Doorbashizadeh (مدل‌سازی پیشرفته در مهندسی عمران)
Modeling and estimating the amount of runoff in an area is very important in water resources management; Because the river flow is one of the important factors in the hydrological cycle, which depends on various factors such as rainfall. In the current research, entropy and fractal criteria were used to determine the runoff trend of the Silakhor plain during the years 1360-1400. In the first step, the amount of entropy was determined for the time period of 1360-1400 runoff parameters. Then it was compared with the amount of entropy obtained for the rainfall parameter. In the next step, Hurst index values, one of the fractal criteria, were calculated for rainfall and runoff parameters in order to check the range of stability and trends.The results of the research show that the runoff entropy fluctuates, but these fluctuations have also been observed in the rainfall variable. In contrast, the Hurst index values ​​of runoff and rainfall parameters are in the range of strong stability (0.5 to 1) and the time series have long-term memory. Fluctuations and irregularities observed in runoff entropy values ​​can be caused by the minimal impact of rainfall and the maximal impact of human intervention and over-harvesting, which can lead to water crises.